Assembly of the salt-secreting mangrove Avicennia rumphiana. - Jeremy R Shearman; Chaiwat Naktang; Chutima Sonthirod; Wasitthee Kongkachana; Sonicha U-Thoomporn; Nukoon Jomchai; Chatree Maknual; Suchart Yamprasai; Poonsri Wanthongchai; Wirulda Pootakham; Sithichoke Tangphatsornruang (PLoS ONE)
Avicennia rumphiana, also known as Avicennia marina var. rumphiana or Avicennia lanata, is a mangrove species that has high salt tolerance and is one of the few species that secretes salt through the leaves, similar to Avicennia marina. We sequenced and assembled the A. rumphiana genome into 24,094 Supernova-scaffolds totalling 499.6 Mb. Sequence comparison showed that 68.7% of the A. rumphiana genome aligned to A. marina sequence, covering 72% of the A. marina genome at an average nucleotide identity of 87.7%, showing that A. marina is closely related to A. rumphiana and, thus, suitable for reference based scaffolding of the A. rumphiana Supernova-scaffolds. Reference based scaffolding produced 32 chromosome-level scaffolds containing 447.3 Mb, with 52.3 Mb of sequence unplaced. Annotation of this genome assembly resulted in 37,347 genes with 22,414 of those contained within chromosome scaffolds. A total of 671 genes matched to genes that are linked to salt tolerance. Genome comparison shows that A. rumphiana is quite different to A. marina and should, therefore, not be referred to as a variant of A. marina.